A practical guide of item generation for food-based social entrepreneurs’ mindset in Malaysia - Sabri, Khairun Najihah; Mohamad, Siti Fatimah; Ungku Zainal Abidin, Ungku Fatimah; Ghazali, Hazrina; Ali@Hamid, Mass Hareeza (UBD School of Business and Economics, 2023)
The practice of social entrepreneurship has gained considerable traction in developing countries, but there is a lack of in-depth research on the subject, particularly regarding the mindset of social entrepreneurs working in the food sector. This study aims to fill this gap by presenting a practical guide for constructing items to assess the mindset of food-based social entrepreneurs in Malaysia. To achieve this objective, qualitative interviews were conducted with social entrepreneurs working in the food sector and key government stakeholders involved in social entrepreneurship. Through a thorough thematic analysis of these interviews, nine overarching themes emerged that offer valuable insights into the mindset of food-based social entrepreneurs in Malaysia. Building on these themes, the researchers generated a comprehensive set of 43 items that capture various dimensions of the mindset component in this context. These items serve as a valuable tool for assessing and understanding the mindset of Malaysian food-based social entrepreneurs. The significance of this study lies in its potential to offer guidance to readers embarking on item development as part of the scale development process, particularly in the field of social entrepreneurship. By providing a practical example of how items can be developed based on qualitative research findings, this study contributes to the broader understanding of social entrepreneurship and supports the advancement of research in the field. Ultimately, it is expected that this study will serve as a valuable resource for academics, practitioners, and policy makers. It will enable them to better comprehend the mindset of food-based social entrepreneurs in Malaysia and facilitate the development of effective strategies and support systems for this growing sector.